1998
DOI: 10.1021/cm980186p
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Triaryldiamines as Thermally Stable Hole Transporting Layers for Organic Light-Emitting Devices

Abstract: The synthesis of a series of asymmetric triaryldiamines has provided a number of materials with a wide range of thermal, electrochemical, and spectroscopic properties. The asymmetric materials described herein have two different diarylamine groups bound to a 1,4-phenylene or 4,4‘-biphenylene core, i.e., Ar1Ar2N−C6H4−NAr1‘Ar3 or Ar1Ar2N-biphenyl-NAr1‘Ar3, respectively. The diarylamines studied include diphenylamine, phenyl-m-tolylamine, naphthylphenylamine, iminostilbene, iminodibenzyl, and carbazole. These mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
200
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(210 citation statements)
references
References 32 publications
9
200
0
1
Order By: Relevance
“…thermal and morphological stability). It is well demonstrated that the thermal stability or glass-state durability of organic compounds could be greatly improved upon incorporation of a carbazole or fused aromatic moiety in the core structure (Kuwabara et al, 1994;Koene et al, 1998;O'Brien et al, 1998). Furthermore, the carbazole moiety can be easily functionalized at its 3-, 6-, or 9-positions and covalently linked to other molecular moieties (Joule, 1984), such as alkyl, phenyl, diarylamine, pyrenyl, etc.…”
Section: Carbazole/arylamine/fluorene/pyrene-composed Hybrids Light-ementioning
confidence: 99%
“…thermal and morphological stability). It is well demonstrated that the thermal stability or glass-state durability of organic compounds could be greatly improved upon incorporation of a carbazole or fused aromatic moiety in the core structure (Kuwabara et al, 1994;Koene et al, 1998;O'Brien et al, 1998). Furthermore, the carbazole moiety can be easily functionalized at its 3-, 6-, or 9-positions and covalently linked to other molecular moieties (Joule, 1984), such as alkyl, phenyl, diarylamine, pyrenyl, etc.…”
Section: Carbazole/arylamine/fluorene/pyrene-composed Hybrids Light-ementioning
confidence: 99%
“…[2][3][4] Recently, considerable efforts have been devoted to the development of new amorphous triarylamines possessing high morphologic stability. [5][6][7][8][9][10] Certain tetraaminobiphenyl derivatives are known to have photoconductive properties. They have been used for electrophotographic applications.…”
mentioning
confidence: 99%
“…The bulk thermal properties of CBP, BCP and TCTA are relatively well known. The glass transition temperature (T g ) of CBP is difficult to determine 130 although it has been reported to be as low as 62 °C 131 but up to 78 °C. 263 BCP, and the related 4,7-diphenyl-1,10-phenanthroline (BPhen), also have glass transition temperatures around 62 °C 255,264 although one report puts the T g of BCP at 83 °C.…”
Section: Resultsmentioning
confidence: 99%
“…protonated CBP. 130 In contrast the emission ( em = 516 nm) from both blend concentrations was entirely from the Ir(ppy) 3 indicating that the Ir(ppy) 3 was distributed such that it was within the diffusion length of an exciton formed on the d-CBP.…”
Section: Ir(ppy) 3 :Cbp Blend Filmsmentioning
confidence: 95%
See 1 more Smart Citation